OCCURRENCE OF Yersinia enterocolitica SEROTYPE O:9, AND Citrobacter freundii, TWO POTENTIAL HUMAN PATHOGENS IN THE THROATS OF TROPICAL PIGS OF GRENADA ORIGIN - Amadi, Victor Anozie; Hariharan, Harry; Matthew-Belmar, Vanessa; Nicholas-Thomas, Roxanne; DeAllie, Claude; Sharma, Ravindra (Bacterial Empire, 2019)
A study to determine the occurrence of Yersinia enterocolitica and Citrobacter freundii, two potential human pathogens in the throats of tropical pigs of Grenada origin and the antimicrobial pattern of the isolates was carried out. During a period of 30 days (15 September 2017 to 15 October 2017), throat swabs from a total of 97 weaned pigs were sampled to isolate and characterize Y. enterocolitica by serotyping and resistance testing, and to isolates C. freundii. Of the pigs tested, four (4.1%) pigs were positive for Y. enterocolitica. The four Yersinia-positive pigs included one (2.4%) of 41 male pigs and three (5.4%) of 56 female pigs. There were no significant differences between the proportions of Yersinia-positive male and female pigs (p = 0.8437). Of these four Yersinia-positive pigs, two were mixed with C. freundii, one had slight contamination, and the other was pure. All belonged to serotype 0:9. There were 31 pigs positive for C. freundii, and all showed mixed growth. Antimicrobial susceptibility tests against 14 drugs indicated that all isolates of Y. enterocolitica were susceptible to third-generation cephalosporins and fluoroquinolones, two classes of antimicrobials recommended for the treatment of Y. enterocolitica infection in humans.